2000
DOI: 10.1111/j.1095-8339.2000.tb01219.x
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral defence strategy: variation of barbaloin content in the succulent leaf parts of Aloe arborescens Miller (Liliaceae)

Abstract: A h a r b m c m is a large, multi-stemmed shrub and is one of the very common Aloe species along the Indian Ocean coast of southern Africa, from the Cape, in the south, to Zimbabwe and Malawi in the north. It is used as a hedge plant to protect agricultural fields or stock and as a horticultural plant in gardens. Barbaloin, a secondary phenolic metabolite, is distributed in the plants as part of a peripheral defence strategy. Barbaloin content was found to be highest in the youngest leaves. Within these, conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Barbaloin and aloe emodin (Sigma Chemical Co., St. Louis, MO, USA) assays were as described (Gutterman & Chauser-Volfson, 2000) with certain modifications. The supernatant of 200 ll was dripped onto pre-coated thin layer chromatographic (TLC) sheets, silica-gel GF 254 on glass (20 · 20 cm) that had been activated at 105°C for 45 min.…”
Section: Barbaloin and Aloe Emodinmentioning
confidence: 99%
See 2 more Smart Citations
“…Barbaloin and aloe emodin (Sigma Chemical Co., St. Louis, MO, USA) assays were as described (Gutterman & Chauser-Volfson, 2000) with certain modifications. The supernatant of 200 ll was dripped onto pre-coated thin layer chromatographic (TLC) sheets, silica-gel GF 254 on glass (20 · 20 cm) that had been activated at 105°C for 45 min.…”
Section: Barbaloin and Aloe Emodinmentioning
confidence: 99%
“…Aloins are generally toxic contaminants in aloe gel used in cosmetics (Gutterman & Chauser-Volfson, 2000). There are also cautionary investigations warning of possible allergic effects on some patients (Reynolds & Dweck, 1999).…”
Section: Influence Of Temperature On the Barbaloin Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly the total sterols were more in micropropagated plants and increases with maturity (0.56 to 2.19 mg g −1 DW). The Gutterman et al (2000) has reported the distribution of secondary phenolic metabolites as a peripheral defense strategy in the succulent leaf parts of Aloe arborescens. Due to stress micropropagative plants had steady state transcript levels for various biosynthetic enzymes resulting in higher secondary metabolite accumulation.…”
mentioning
confidence: 99%
“…The main anthraquinones present in Aloe vera are aloin, aloe amodin, aloe bitter and aloe lectin (Wang 2009). It has been reported that aloin constitutes up to 30% of the dried leaf exudates (Groom & Reynolds 1986) and that aloin plays an important role in defense mechanisms against herbivores (Gutterman & Volfson 2000). In small quantities, anthraquinones act as antimicrobial (Lorenzetts et al 1964) and antiviral agents (Sims et al 1971).…”
Section: Introductionmentioning
confidence: 99%